Safety Profile Standardization and HPTLC Fingerprint Analysis of Dioscorea bulbifera Linn - Subasini Uthirapathy, Dr (International Journal of Pharmaceutical & Biological Archive, 2016)
Safety Profile Standardization and HPTLC Fingerprint Analysis of Dioscorea bulbifera Linn